The Northern Giardini / Nurul Azwa Sharidan ... [et al.] - Sharidan, Nurul Azwa; Shahruddin, Nurul Najihah; Niamat, Nur Irdina Syahirah; Ahmad, Norfazillah (2024)
University students often face the challenge of balancing academic demands with personal well-being. With busy schedules and academic pressure, students may find it difficult to carve out time for relaxation and rejuvenation. This lack of space to unwind can contribute to increased stress levels, impacting both mental and physical health. Providing designated areas or pavilions for students to relax and recharge can address this issue, offering a sanctuary where they can briefly escape the rigours of university life and promote overall well-being.